1984
DOI: 10.4315/0362-028x-47.9.690
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Activity During Storage of Human Milk: Accumulation of Free Fatty Acids

Abstract: Lipolysis was quantitated during storage of fluid and freezedried human whole and skim milks. Fatty acid accumulation was faster in whole fluid milk stored for 1 week at 4°C than in frozen (−20°C) samples stored for 180 d. The rapid accumulation of fatty acids during 24 h of storage at 4°C was enhanced in previously frozen milk samples. While freeze-dried whole milk showed no lipolysis when stored at −20°C, accumulation of free fatty acids was rapid in samples stored at room temperature. Fluid and freeze-dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Storing breast milk at 4°C increases the free fatty acid content significantly from 51% to 454% after 24 hours [51,78,81], from 76% to 502% after 48 hours [51,78], from 85% to 101% after 72 hours [82] and by 265% after 96 hours [50], although breast milk samples in the latter study were stored at -80°C after refrigeration, until subsequent free fatty acid analysis [50]. In a time course experiment, higher free fatty acid levels were seen at 48 hours compared to 24 hours, although not statistically significant, whereas levels were significantly higher at 72 hours, with the greatest increases seen with omega-3 PUFAs [51].…”
Section: Free Fatty Acid Levelsmentioning
confidence: 99%
“…Storing breast milk at 4°C increases the free fatty acid content significantly from 51% to 454% after 24 hours [51,78,81], from 76% to 502% after 48 hours [51,78], from 85% to 101% after 72 hours [82] and by 265% after 96 hours [50], although breast milk samples in the latter study were stored at -80°C after refrigeration, until subsequent free fatty acid analysis [50]. In a time course experiment, higher free fatty acid levels were seen at 48 hours compared to 24 hours, although not statistically significant, whereas levels were significantly higher at 72 hours, with the greatest increases seen with omega-3 PUFAs [51].…”
Section: Free Fatty Acid Levelsmentioning
confidence: 99%
“…[29] showed that lipoprotein lipase and bile-salt-stimulated lipase remain active after the storage of raw milk at −20 • C for 5 months and lead to hydrolysis of the milk fat. Presumably, the higher the temperature, the higher the activity of these enzymes will be [30]; hence, the greatest changes are observed at the highest temperature used. It is interesting that HS-ST of the HM did not change its fat content.…”
Section: Effect Of Hs-st On Fat and The Energy Valuementioning
confidence: 99%
“…Key Words: Human milk-Fatty acids-Lactation. at temperatures greater than -25°C (6)(7)(8). Most previous studies report the release of total fatty acids in milk during storage without identifying individual fatty acids.…”
mentioning
confidence: 99%